A randomized trial of a pain management intervention for adults receiving substance use disorder treatment. (15th April 2016) - Ilgen, Mark A.; Bohnert, Amy S. B.; Chermack, Stephen; Conran, Carly; Jannausch, Mary; Trafton, Jodie; Blow, Frederic C.
Abstract: Background and Aims: Chronic pain is difficult to treat in individuals with substance use disorders and, when not resolved, can have a negative impact on substance use disorder treatment outcomes. This study tested the efficacy of a psychosocial pain management intervention, ImPAT (improving pain during addiction treatment), that combines pain management with content related to managing pain without substance use. Design: Single‐site, parallel‐groups randomized controlled trial comparing ImPAT to a supportive psychoeducational control (SPC) condition; follow‐up assessments occurred at 3, 6 and 12 months. Setting: The Ann Arbor VA Substance Use Disorder treatment program, USA. Participants: Veterans Health Administration patients { n  = 129; mean [standard deviation (SD)], age = 51.7 (9.5); 115 of 129 (89%) male; ImPAT ( n  = 65); SPC ( n  = 64)}. Intervention: ImPAT combines principles of cognitive–behavioral therapy and acceptance‐based approaches to pain management with content related to avoiding the use of substances as a coping mechanism for pain. The SPC used a psychoeducational attention control treatment for alcoholism modified to cover other substances in addition to alcohol. Measurements: Primary: Pain intensity over 12 months; secondary: pain‐related functioning, frequency of alcohol and drug use over 12 months. Findings: Primary: randomization to the ImPAT intervention versus SPC predicted significantly lower pain intensity {β [standard error (SE)] = −0.71 (0.29); 95% confidence interval (CI) = −1.29, −0.12}; secondary: relative to the SPC condition, those who received ImPAT also reported improved pain‐related functioning [β (SE) = 0.27 (0.11); 95% CI = 0.05, 0.49] and lower frequency of alcohol consumption [β (SE) = −0.77; 95% CI = −1.34, −0.20]. No differences were found between conditions on frequency of drug use over follow‐up. Conclusions: For adults with pain who are enrolled in addictions treatment, receipt of a psychological pain management intervention (improving pain during addiction treatment) reduced pain and alcohol use and improves pain‐related functioning over 12 months relative to a matched‐attention control condition.